Research Systematic Narrative Literature Review Artifact Analysis of the Application of Agile Scrum Method in the Development of Web-based Information Systems - Eko Siswo Adi Sahputra (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
Using the Narrative Literature Review (NLR) method, this study aims to evaluate the suitability of the application of the Scrum framework in software development with predetermined rules. The research focuses on Scrum artifacts, namely Product Backlog, Sprint Backlog, and Product Increment. The research data was obtained from journals in Google Scholar that are relevant to the implementation of Agile Scrum in software development. The results of this research are expected to provide a better understanding of the criteria and rules that must be met in order for a framework to be considered a Scrum framework. This research will specifically examine the suitability of artifacts in implementation with applicable Scrum rules. Based on a review of 10 literature journals, the main focus is on artifacts. Most implementations of the Product Backlog do not include tasks in the backlog and are not sorted by highest priority to lowest. In the Sprint Backlog the status of the list of tasks in progress is not displayed in the backlog sprint, there is no ownership of the task, and in the Product Increment, tasks that have been completed at the end of the sprint and unfinished tasks that will be continued in the next sprint cannot be displayed. Sprint goals are also not displayed on the Sprint Backlog, so in the end it is not possible to measure the agility of Agile Scrum.